Gold mountain - Yee, Betty G., 1966- (Carolrhoda Lab, 2022)
Fifteen-year-old Chinese Tam Ling Fan poses as her deceased brother Jing to take a job as a laborer on the transcontinental railroad in 1867 America. She hopes to secure enough money to free her jailed father who was falsely accused of treason. However, Tam underestimates how hard and dangerous the work is, and uses everything in her power to keep her secret and survive the racism around her.